Identification Of Naqli Knowledge During Motivational Session For Periodontitis Patients: A Qualitative Study - Mat Baharin, Nor Haliza; Wan Abdul Aziz, Wan Nur Alwani; Ramli, Haslinda (IIUM Medical Journal Malaysia, 2017)
Introduction: Integrated approach of naqli and aqli knowledge is applied in most educational activities conducted in Faculty of Dentistry, Universiti Sains Islam Malaysia (USIM). Naqli is knowledge from al-Quran and as-Sunnah while aqli is rational knowledge or knowledge based on scientific evidence. Currently the integration of naqli and aqli knowledge in periodontology subject is at the initial stage of implementation. Motivational session for periodontitis patients is identified to be one of the educational activities that integrates the naqli and aqli knowledge. Therefore, this study is aimed to identify elements of naqli knowledge that can be included during motivational session in periodontal clinic. Materials and Methods: All consented Year Four Students in Faculty of Dentistry, USIM were subjected to an open ended interview. A qualitative method used was grounded theory which focused on the elements of naqli knowledge that may be incorporated in motivational session. The recorded interview was transcribed and analysed with constant comparison.Results: From the interview, it was found that hadith on importance and practice of siwak should be included as it may boost patients motivation towards periodontal care. The importance on taking care of the teeth as an amanah is another element identified that may change the patients attitude towards oral care. The frequency of brushing related with wudhuk and it sunnah was also recognized to assist patients in their daily oral care. Conclusion(s): For conclusion, the integration of naqli and aqli knowledge during motivational session is possible and it may upsurge patients motivation.